If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -20 = 2x + -5 Reorder the terms: -20 + 3x = 2x + -5 Reorder the terms: -20 + 3x = -5 + 2x Solving -20 + 3x = -5 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -20 + 3x + -2x = -5 + 2x + -2x Combine like terms: 3x + -2x = 1x -20 + 1x = -5 + 2x + -2x Combine like terms: 2x + -2x = 0 -20 + 1x = -5 + 0 -20 + 1x = -5 Add '20' to each side of the equation. -20 + 20 + 1x = -5 + 20 Combine like terms: -20 + 20 = 0 0 + 1x = -5 + 20 1x = -5 + 20 Combine like terms: -5 + 20 = 15 1x = 15 Divide each side by '1'. x = 15 Simplifying x = 15
| 6x+13=17x+18 | | 9.6=x/4 | | 27x^4+64x=0 | | 5x+12=16x+17 | | 7(3+4r)=-33 | | (x-5)(x+1)(x+3i)=0 | | f(x)=(x+1)(x-3)(x-3-4i)(x-3+4i) | | -2v^2+3v-1=0 | | (9t+5)=10*6t | | 5-6d=-9 | | 3td=12t | | 0.2(n-3.2)=3 | | 12-x+4x^2-9x^7=0 | | 3(3x)+2(5)=6x-500 | | 3(x+2.2)=13.5 | | X-8=6-x | | -x+4=3x+2x-8 | | 7(-17)2-6(-17)=-27+12 | | -5x^2+24x+36=0 | | 18-3x=-8x+13 | | 2xsquared-11x=-15 | | -4x-1=-7x-4 | | 7c+2-6c=-27+12 | | 0.20y+24+15=46 | | 4x^2+4y^2-24=0 | | 4x^2+4y^2=24 | | (8x^2/3)^3= | | -4b-2=2b-2b | | 5x-4(x-7)=34 | | -7x+32=21 | | 4(y+3)=y+24 | | 2m+20=3m+8 |